2014
DOI: 10.2478/bjmg-2014-0022
|View full text |Cite
|
Sign up to set email alerts
|

Does the A9285g Polymorphism in Collagen Type XII α1 Gene Associate with the Risk of Anterior Cruciate Ligament Ruptures?

Abstract: One of the most severe injuries sustained by athletes is rupture of the anterior cruciate ligament (ACL). Recent investigations suggest that a predisposition for ACL rupture may be the result of specific genetic sequence variants. In light of this, we decided to investigate whether the COL12A1 A9285G polymorphism was associated with ACL ruptures in Polish football players.We compared genotypic and allelic frequencies of the COL12A1 A9285G polymorphism in two groups of athletes: 91 male football players (23 ± 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Subsequent investigators conducted similar case-control genetic association studies in an Asian or Caucasian population, but studies did not yield consistent results. In their studies, Ficek et al (2014) andO'Connell et al (2015) basically concluded similar results to Posthumus et al, that the AA genotype of rs970547 was associated with increased risk of ACLR in female, but not male participants or the whole population, and it was worth noting that the main subjects of these studies were Caucasians. For the remaining studies, the conclusions were contradictory to the above studies.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Subsequent investigators conducted similar case-control genetic association studies in an Asian or Caucasian population, but studies did not yield consistent results. In their studies, Ficek et al (2014) andO'Connell et al (2015) basically concluded similar results to Posthumus et al, that the AA genotype of rs970547 was associated with increased risk of ACLR in female, but not male participants or the whole population, and it was worth noting that the main subjects of these studies were Caucasians. For the remaining studies, the conclusions were contradictory to the above studies.…”
Section: Discussionsupporting
confidence: 64%
“…Prior to combining data from each individual study, we applied a "model-free approach" to estimate the genetic effect of rs970547 on risk of ACLR. Seven studies (Posthumus et al, 2010;Ficek et al, 2014;O'Connell et al, 2015;John et al, 2016b;Kang et al, 2019;Sivertsen et al, 2019;Zhao et al, 2020) including eight independent cohorts provided detailed genotype counts in both the ACLR group and the control group, and therefore OR1, OR2, and OR3 were calculated to capture the magnitude of genetic was marginally significant. Based on the relationships between these three pairwise comparisons, rs970547 was not significantly associated with risk of ACLR.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
“…Ficek et al [39] 91 Polish male football players with surgically diagnosed primary ACL ruptures who qualified for ligament reconstruction; 143 male football players of a similar age without any self-reported history of ligament or tendon injury…”
Section: Col1a1mentioning
confidence: 99%
“…The studies presented in Table 4 imply that COL1A1, COL12A1, and COL5A1 G-T haplotypes are associated with reduced ACL injury risk [37][38][39][40]. This suggests that harbouring this haplotype might provide a protective effect against injuries among professional football players.…”
Section: Anterior Cruciate Ligament Injuriesmentioning
confidence: 99%
“…Multiple extrinsic [ 5 ] and intrinsic risk factors have been associated with anterior cruciate ligament (ACL) ruptures [ 6 ] and more recently, evidence implicating genetic susceptibility as an intrinsic risk factor has been shown [ 7 ]. Specifically, roles of the COL1A1 gene [ 8 ], COL5A1 gene [ 9 , 10 ], COL12A1 gene [ 11 , 12 ], and the chromosome 11 MMP gene cluster [ 13 ] have been suggested, to name only a few loci. Although a number of authors claim that greater core stability decreases the risk of ACLR, the search for genetic determinants of susceptibility to ACL rupture continues.…”
Section: Introductionmentioning
confidence: 99%